Impact of Strategical Sustainability on Real Estate Industry’s Sustainability Performance - Sanchaniya Rashmi Jaymin; Geipele Ineta (Foundations of Management)
The primary aim of this research is to investigate the relationship between strategic sustainability and firm success within the real estate sector. Specifically, it aims to assess how strategic sustainability factors, notably business strategy and management, influence sustainability performance. By exploring this uncharted territory, the study seeks to provide insights into the role of strategic sustainability in enhancing an intangible value in terms of sustainability performance. Through quantitative data gathered from the Latvian real estate industry, the research study demonstrates that greater emphasis on business strategy efforts and activities is positively associated with improved sustainability performance. Moreover, it establishes a correlation between enhanced management practices and higher sustainability performance. Ultimately, this research contributes to our understanding of how strategic sustainability can drive the long-term sustainability and success of real estate businesses, benefitting regions, nations, and the global community.